IMPLEMENTATION OF PRODUCT QUALITY AND INTERESTS IN DOING WORD OF MOUTH IN ARK RESTAURANT, MALAYSIA (Case Study of STIE Students Sutaatmadja 2019 KKL Participants) - Grace Wijayanti; Muhammad Rayhan Fauzan; Devy Widya Apriandi; Bismantara Bismantara (STIESA Press, 2020)
This study aims to describe implementation product quality and interest doing word of mouth at Ark Restaurant, Malaysia by studying case of STIE Sutaamadja college student which member of KKL (Kuliah Kerja Lapangan) 2019. This study used data collection techniques namely observation, questionnaires, and literature study. The observation to measuring quality product in Ark Restaurant. The population used in this research is college students in STIE Sutaatmadja and also member of KKL (Kuliah Kerja Lapangan) in 2019 who were consumers at Ark Restaurant. This research had ? = 5%. The questionnaire was distributed to sample to examine the interests doing word of mouth. The literature study to collect theories and supporting data.the results of this research are that overall product quality is good and overall interests of word of mouth is good. Overall, the interest in doing word of mouth was good at an average percentage of 89%.